(3fXGe GdMSGHGJ GdEbJUGOjI GdLRGFQjI f(B.(3M(B.(3E(B.(3L eOYe HYOO ef GdCeKdI hGdJeGQjf GdeMdhdIs - (3bGOI(B, (3bGSes ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2002)
(3GdeMGSHI GdhWfjI(B- (3GdYQV GdYGe dfXGe GdMSGHGJ GdEbJUGOjI GdLRGFQjI (B-(3fXGe GdeMGSHI GdhWfjI(B.s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdYGeIs